(untitled) (Literatures of the World: Poetics, Mentality and Spirituality, 2017)
The features of novelistic composition in the works of Austrian writer A. Shtifter are analyzed in the article. Shtifter was called an Austrian contemporary of literary prose, as his work accounts to the first half of the XIX century. The artistic structure and specificity of novels and short stories of writer is considered.